Quantificação da incerteza em cadeia integrada de modelos hidrológicos e viabilidade operacional: modelos climáticos, hidrológicos e aprendizagem de máquina no contexto das mudanças climáticas - Estácio, Ályson Brayner Sousa (2023)
The assessment of water supply is fundamental for the planning and management of water resources. However, the set of data, methods and models used to produce hydrological information and, in particular, to assess water supply is embedded with uncertainty. On the one hand, quantifying this uncertainty is essential for more robust decision-making. On the other hand, the way in which uncertainty is explained and communicated is a challenge for the operational viability of decision-making. The objective of this study is to integrate uncertainty quantification and operational viability with the production of hydrological information for the assessment of water supply. To this end, new methods and concepts are proposed, applied to the surface water resources system in the State of Ceará. The assessment of water supply combined the calibration of hydrological models, the regionalization of parameters and the optimization of the reservoir network. Three hydrological models on a daily scale (SMAP, GR4J and SAC-SMA) were calibrated for a set of thirty basins and for three objective functions. Using the calibrated parameters, Machine Learning models were trained to regionalize parameters. The uncertainties associated with the regionalized parameters were evaluated using the different regionalization methods and objective functions. Specific strategies for each regionalization method were adopted to ensure parsimony and operational viability. Using the regionalized parameters, historical series of inflow to strategic reservoirs in Ceará were calculated and series were projected for the 21st century, subject to climate change. CMIP6 General Circulation Models were used in the projections. The current and projected water supplies were calculated in the form of regularized flow based on the optimization of the reservoir network. According to the results, GR4J and SAC-SMA are superior to SMAP. The methods of regionalização aplicados afetaram com diferentes intensidades a correlação entre os parâmetros, o que não comprometeu a correlação espacial das vazões. Os parâmetros do modelo hidrológico mantêm relação com a física da bacia. As incertezas do método de regionalização e dos parâmetros calibrados, usados como referência para a regionalização, mostraram-se ambas relevantes na contabilização da incerteza dos parâmetros regionalizados. As projeções climáticas apontam para um aumento da vazão regularizada acompanhado por um aumento substancial da incerteza. Se incorporada uma análise de risco, a oferta hídrica da região analisada pode, a depender do nível de risco admissível adotado, ser reduzida. As incertezas da oferta hídrica projetada são resultantes, principalmente, da incerteza climática. A metodologia aplicada no trabalho contribui para a gestão dos recursos hídricos no Ceará, ao mesmo tempo em que os conceitos e métodos desenvolvidos devem enriquecer as discussões sobre a produção de informação hidrológica no contexto científico e em outros sistemas de recursos hídricos.